Catalytic effect and mechanism of NiCu solid solutions on hydrogen storage properties of MgH2. (July 2020) - Zhang, J.; He, L.; Yao, Y.; Zhou, X.J.; Yu, L.P.; Lu, X.Z.; Zhou, D.W.
Abstract: In this work, the NiCu solid solutions with different Ni/Cu molar ratios were prepared and then doped into MgH2 through ball milling to modify its hydrogen sorption properties. The experimental results show that the Ni–25%Cu and Ni–50%Cu exhibit the superior catalytic effect over pure Ni, pure Cu and Ni–75%Cu on the dehydrogenation of MgH2 . Among them, the 5h-milled MgH2 /Ni–50%Cu system starts to desorb hydrogen at 205.8 °C, which is about 96.9 °C lower than that of as-milled pristine MgH2 . Moreover, the MgH2 /Ni-50% Cu system can release 5.14 wt% hydrogen at 300 °C within 15 min, while MgH2 can only release 2.92 wt% hydrogen under the same condition. More importantly, the dehydrogenated MgH2 /Ni–50%Cu can reabsorb 4.37 wt% hydrogen even at 250 °C for 30 min. The enhanced hydrogen sorption kinetics of MgH2 /Ni–50%Cu mainly attributes to the "hydrogen spillover" effect of in - situ formed Mg2 Ni(Cu) phases. Further theoretical calculations reveal that the strong interactions between H and Ni/Cu result in the weakened stability of MgH2, decreased bond strength of Mg–H and enhanced dehydrogenation properties of MgH2 . This research provides an important guidance for design multiple transition metals catalysts to improve efficiently hydrogen storage properties of magnesium-based and other metal-based hydrides. Highlights: Influence of NiCu solid solutions on hydrogen storage properties of MgH2 are studied. The Ni–50%Cu exhibits the superior catalytic effect on hydrogen sorption of MgH2 . The in - situ formed Mg2 Ni(Cu) phases play "hydrogen spillover" effect on Mg/MgH2 . The doping of Ni/Cu weakens stability of MgH2 and decreased bond strength of Mg–H.